El juego coreográfico escénico: propuesta didáctica, en manos de la maestra Martha Lucía Jiménez Gutiérrez (2024)
This research explores the influence of the pedagogical and artistic training of Martha Lucía Jiménez Gutiérrez in creating a didactic of her own in the field of dance, focusing on her innovative concept of "choreographic play". Through a qualitative approach, it will be analysed how your experience with recognized teachers has enriched your teaching practice and enabled the integration of dance, theatre and music in the teaching-learning process. The research includes interviews and classroom observations to understand the methodologies that Jiménez uses, promoting active and meaningful learning that fosters cultural identity and artistic expression of his students. The results are expected to not only validate your teaching approach as an effective strategy.